Genomic epidemiology of Rift Valley fever virus involved in the 2018 and 2022 outbreaks in livestock in Rwanda - Nsengimana, I.; Juma, John; Roesel, Kristina; Gasana, M.N.; Ndayisenga, F.; Muvunyi, C.M.; Hakizimana, E.; Hakizimana, J.N.; Eastwood, G.; Chengula, A.A.; Bett, Bernard K.; Kasanga, C.J.; et al. (MDPI, 2024)
Rift Valley fever (RVF), a mosquito-borne transboundary zoonosis, was first confirmed in Rwanda’s livestock in 2012 and since then sporadic cases have been reported almost every year. In 2018, the country experienced its first large outbreak, which was followed by a second one in 2022. To determine the circulating virus lineages and their ancestral origin, two genome sequences from the 2018 outbreak, and thirty-six, forty-one, and thirty-eight sequences of small (S), medium (M), and large (L) genome segments, respectively, from the 2022 outbreak were generated. All of the samples from the 2022 outbreak were collected from slaughterhouses. Both maximum likelihood and Bayesian-based phylogenetic analyses were performed. The findings showed that RVF viruses belonging to a single lineage, C, were circulating during the two outbreaks, and shared a recent common ancestor with RVF viruses isolated in Uganda between 2016 and 2019, and were also linked to the 2006/2007 largest East Africa RVF outbreak reported in Kenya, Tanzania, and Somalia. Alongside the wild-type viruses, genetic evidence of the RVFV Clone 13 vaccine strain was found in slaughterhouse animals, demonstrating a possible occupational risk of exposure with unknown outcome for people working in meat-related industry. These results provide additional evidence of the ongoing wide spread of RVFV lineage C in Africa and emphasize the need for an effective national and international One Health-based collaborative approach in responding to RVF emergencies.